Mobile Ad Hoc Networking Issues and Challenges - Dalisay, Ferdinand (Southeast Asian Journal of Science and Technology, 2017)
MANET has the following characteristics: “open network boundary, dynamic topology, distributed network, fast and quick implementation and hop-by-hop communications”. These features made MANET vulnerable to different issues and challenges. This paper outlines the different issues and challenges in MANET and are categorized as follows: (1) security, (2) routing, (3) topology control and (4) energy efficiency. A comprehensive analysis of several research papers discussing the issues and challenges, categorized per area, is presented.